Kembalinya Subyek: Sosiologi Memaknai Kembali Multikulturalisme - Kusumadewi, Lucia Ratih (UI Scholars Hub, 2010)
The idea of modern society that has been dominated for long time by political idea (read: state) fails since state has lost her control over economy. The state loses as well control over her socio-cultural legitimacy while society became more plural. Sociologists in 80’s inspired by Tourianian’s idea, find that in an ‘ultra-modern’ society, the redefinition on the idea of society, modernity and rationality are inevitable and ‘the return of the Subject’ shall be a main agenda for further sociological analysis. In this context how multiculturalism might be construed? This article has been in attempt to explore the reconstitution of multiculturalism idea based on the new paradigm concerning the return of the Subject, which at the moment is a real challenge for sociology